Transformation of Da’wah and Counseling from the Traditional Era to the Digital Era - Dwitasari, Nirinda; Velicyela Arianto, April (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
This study discusses the transformation of da’wah and counseling from the traditional era to the digital era, which has brought significant changes to communication methods and the effectiveness of services. Da’wah, which was previously delivered through face-to-face sermons, has now evolved into digital platforms such as social media, podcasts, and video streaming, enabling a wider reach—especially among younger audiences. Meanwhile, counseling services have also undergone digitalization through online platforms that allow more flexible and efficient access for the public. This study employs a descriptive qualitative method with a library research approach, analyzing relevant literature from 2019–2025. The findings indicate that the use of communication technology plays a crucial role in enhancing the reach and effectiveness of both da’wah and counseling. However, it also presents challenges such as popularity orientation, limited emotional interaction, data privacy risks, and low digital literacy. Therefore, adaptive strategies are needed to balance technological innovation with spiritual values and professional ethics, ensuring that digital da’wah and counseling remain high-quality, relevant, and meaningful to society.